Wouldn’t Mendelson Work Something Out? – Genesis of Polish Socialist Party of the Prussian Partition in the Light of Connections with London’s Socialists - Olejnik, Oskar (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
Article approaches a try to define relationship between two Polish socialist groupings – one created around personality of Stanislaw Mendelson, in London, and the other one in Berlin from which the Polish Socialist Party in Prussian Partition arose. The existing historiography poses a background for the research. Basing on archives and reminiscence a try was taken to recreate relationship between these two groupings. The analysis points out the existence of financial, personal and ideological relations. These factors make one realize the subjection of Berlin socialists to Mendelson’s environment.